Effect of Enzymatically Modified Isoquercitrin, a Flavonoid, on Symptoms of Japanese Cedar Pollinosis: A Randomized Double-Blind Placebo-Controlled Trial - Kawai, Mari; Hirano, Toru; Arimitsu, Junsuke; Higa, Shinji; Kuwahara, Yusuke; Hagihara, Keisuke; Shima, Yoshihito; Narazaki, Masashi; Ogata, Atsushi; Koyanagi, Mihoko; Kai, Tomoko; Shimizu, Ryosuke; et al. (International archives of allergy and immunology, 2009)
Background: Flavonoids exert antiallergic and antioxidant effects. We investigated the efficacy of enzymatically modified isoquercitrin (EMIQ), a flavonoid, to relieve symptoms of pollinosis. Methods: In a parallel-group, double-blind placebo-controlled study design, 20 subjects with Japanese cedar pollinosis took two capsules daily of 100 mg EMIQ or a placebo for 8 weeks during the pollen season. Subjective symptoms and activities of daily living (ADL) scores were recorded every day, and the quality of life (QOL) score was obtained every 4 weeks. Blood sampling was performed before and after the study to measure serum cytokines, chemokines, IgE, quercetin and oxidized biomarkers. Results: During the entire study period, total ocular score and ocular itching score for the EMIQ group were significantly lower (p < 0.05) than for the placebo group. When limited to the individual periods, total symptom score for the EMIQ group was significantly lower (p < 0.05, week 4–5) than that for the placebo group while other scores for the EMIQ group, such as total nasal score (p = 0.06, week 4–5), nasal obstruction score (p = 0.08, week 4–5), lacrimation score (p = 0.06, week 5–6), ocular congestion score (p = 0.08, week 4–7) and ADL score (p = 0.08, week 4–7), all tended to be lower. The levels of serum cytokines such as interleukin (IL)-4, IL-5, IL-12, IL-13, interferon-γ, and eotaxin and IgE were not significantly downregulated by the intake of EMIQ but the serum concentrations of oxidized low-density lipoprotein and thymus and activation-regulated chemokine were reduced. Conclusion: Intake of the quercetin glycoside EMIQ was safe and influenced ocular symptoms caused by pollinosis.